Muenke syndrome: An international multicenter natural history study. Issue 4 (6th January 2016) - Kruszka, Paul; Addissie, Yonit A.; Yarnell, Colin M. P.; Hadley, Donald W.; Guillen Sacoto, Maria J.; Platte, Petra; Paelecke, Yvonne; Collmann, Hartmut; Snow, Nicole; Schweitzer, Tilmann; Boyadjiev, Simeon A.; Aravidis, Christos; et al.
Abstract : Muenke syndrome is an autosomal dominant disorder characterized by coronal suture craniosynostosis, hearing loss, developmental delay, carpal, and calcaneal fusions, and behavioral differences. Reduced penetrance and variable expressivity contribute to the wide spectrum of clinical findings. Muenke syndrome constitutes the most common syndromic form of craniosynostosis, with an incidence of 1 in 30, 000 births and is defined by the presence of the p.Pro250Arg mutation in FGFR3 . Participants were recruited from international craniofacial surgery and genetic clinics. Affected individuals, parents, and their siblings, if available, were enrolled in the study if they had a p.Pro250Arg mutation in FGFR3 . One hundred and six patients from 71 families participated in this study. In 51 informative probands, 33 cases (64.7%) were inherited. Eighty‐five percent of the participants had craniosynostosis (16 of 103 did not have craniosynostosis), with 47.5% having bilateral and 28.2% with unilateral synostosis. Females and males were similarly affected with bicoronal craniosynostosis, 50% versus 44.4% ( P  = 0.84), respectively. Clefting was rare (1.1%). Hearing loss was identified in 70.8%, developmental delay in 66.3%, intellectual disability in 35.6%, attention deficit/hyperactivity disorder in 23.7%, and seizures in 20.2%. In patients with complete skeletal surveys (upper and lower extremity x‐rays), 75% of individuals were found to have at least a single abnormal radiographical finding in addition to skull findings. This is the largest study of the natural history of Muenke syndrome, adding valuable clinical information to the care of these individuals including behavioral and cognitive impairment data, vision changes, and hearing loss. © 2016 Wiley Periodicals, Inc.